Retificação de compósito de matriz epóxi reforçado com tecido natural de Rami com e sem óxido grafeno - Abrão, Amanda Souza (2025)
In recent years there has been noticed an increase in the study of composite materials reinforced with natural fibers, which have been promising alternatives for the development of projects and products, such as automobile, aircraft and ship parts, among others. These materials provide excellent mechanical properties to the component and allow flexibility in the design of more complex parts. Moreover, most composite materials reinforced with natural fibers are less expensive than synthetic materials and they are often renewable and recyclable, thus in accordance with the three pillars of sustainability: economic, social and environmental. Due to the working conditions that composites are subjected and considering that many components made from these materials need to be machined to present good finishing and low dimensional deviations, grinding process becomes an alternative. Grinding allows the production of parts with a combination of low roughness values (Ra ≤1.6 µm) and tight dimensional tolerances (Internation Tolerance grade in the range from IT6 to IT3). In this context, the present study aims to evaluate the grindability of epoxy matrix composites reinforced with natural ramie fibers with and without graphene oxide. A silicon carbide grinding wheel was used, two radial depth of cut values (25 and 50 μm), workspeed (2.7 and 7.5 m/min) and overlap ratio values (3 and 8) were tested. As output variables, roughness parameters Ra, Rq, Rt, and Rz, microhardness of the parts, images of the ground surfaces, and grinding power were analyzed. In general, the results showed that, regardless of the values of radial depth of cut, workspeed and overlap ratio values used, the Ra roughness value remained practically constant and below 1.6 μm. Microhardness practically was not affected by the alteration in cutting parameters. Additionally, images of the ground surfaces indicated that, in general, the samples exhibited marks in the grinding direction, some surface imperfections and pores. These results demonstrate that the cutting conditions analyzed did not negatively influence the surface integrity of the parts, unlike what typically occurs when machining metals, particularly cast irons, under similar cutting conditions. Regarding grinding power, it increased with radial depth of cut.